2021
DOI: 10.1038/s41467-021-24195-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Selective inheritance of target genes from only one parent of sexually reproduced F1 progeny in Arabidopsis

Abstract: Sexual reproduction constrains progeny to inherit allelic genes from both parents. Selective acquisition of target genes from only one parent in the F1 generation of plants has many potential applications including the elimination of undesired alleles and acceleration of trait stacking. CRISPR/Cas9-based gene drives can generate biased transmission of a preferred allele and convert heterozygotes to homozygotes in insects and mice, but similar strategies have not been implementable in plants because of a lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In a previous study, we have demonstrated that induction of DSBs using CRISPR-Cas9 can lead to up to 14% of inter-homolog recombination (IHR) in somatic cells at the Psy1 locus of tomato [23]. In Arabidopsis, a recent study also showed that IHR can be used for DSB repair, generating gene conversion, or a gene drive [24]. This was shown in a transgenic system and IHR-mediated DSB repair has not been analyzed yet for endogenous loci in Arabisopsis.…”
Section: Of 15mentioning
confidence: 99%
“…In a previous study, we have demonstrated that induction of DSBs using CRISPR-Cas9 can lead to up to 14% of inter-homolog recombination (IHR) in somatic cells at the Psy1 locus of tomato [23]. In Arabidopsis, a recent study also showed that IHR can be used for DSB repair, generating gene conversion, or a gene drive [24]. This was shown in a transgenic system and IHR-mediated DSB repair has not been analyzed yet for endogenous loci in Arabisopsis.…”
Section: Of 15mentioning
confidence: 99%
“…Though the most rapid progress has been in Anopheles mosquitoes for reduction of vector-borne disease [5][6][7] (for which modification drives have also been developed [8][9][10]), suppression gene drives could also be used to remove invasive species or agricultural pests. Thus far, gene drives have been demonstrated in a variety of organisms, including yeast [11,12], flies [13][14][15][16][17][18], mice [19] and plants [20]. Most of these have been homing type drives, where a nuclease, usually CRISPR/Cas9, cuts a wild-type chromosome at a site-directed by its guide RNA (gRNA) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Though the most rapid progress has been in Anopheles mosquitoes for reduction of vector-borne disease 57 (for which modification drives have also been developed 810 ), suppression gene drives could also be used to remove invasive species or agricultural pests. Thus far, gene drives have been demonstrated in a variety of organisms, including yeast 11,12 , flies 13151618 , mice 19 , and plants 20 . Most of these have been homing types drives, where a nuclease, usually CRISPR/Cas9, cuts a wild-type chromosome at a site directed by its guide RNA (gRNA) 21 .…”
Section: Introductionmentioning
confidence: 99%